METHODS OF TAKING INTO ACCOUNT THE INDIVIDUAL CHARACTERISTICS OF STUDENTS IN PRIMARY GRADES (World Bulletin of Education and Learning, 2025)
This article discusses effective methods of considering students’ individual characteristics in primary education. The primary stage of education plays a significant role in the formation of a child’s personality. Therefore, applying approaches that correspond to students’ age, psychological, intellectual characteristics, and interests increases the effectiveness of the learning process. The article analyzes ways to develop each student’s potential through differentiated instruction, individual tasks, observation and diagnostics, as well as the use of interactive teaching methods. The importance of the teacher’s pedagogical skills and individual approach in developing students’ independent thinking and positive attitudes toward learning is emphasized.
Keywords: Primary education, individual approach, differentiated instruction, student characteristics, pedagogical methods.